An Empirical Study of the Relationship Among Job Satisfaction, Organizational Commitment and Turnover Intention - Sinem Aydogdu; Baris Asikgil (International Review of Management and Marketing, 2011)
This study conducted on 100 employees from production sector and 82 employees from service provider sector. The relationship among job satisfaction, organizational commitment and turnover intention are investigated to determine statistically significant relations. The results of the study support the hypotheses. Job Satisfaction has a significant and positive relationship with three dimensions of organizational commitment and turnover intention has a significant and negative relationship with job satisfaction and organizational commitment.